The Influence Of Sharia Financial Literacy On The Doom Spending Behavior Of Generation Z Students Using E-Commerce - Fatiya Febina Sitepu; Maidalena Maidalena; Muhammad Lathief Ilhamy Nasution (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The rapid growth of e-commerce among Generation Z has changed consumer behavior and given rise to the phenomenon of doom spending, a form of impulsive shopping triggered by emotional stress, economic uncertainty, and the intensity of digital promotions. In the context of Muslim students, Islamic financial literacy is seen as a crucial factor potentially influencing consumer behavior amidst the ease of transactions on digital platforms. This study aims to analyze the influence of Islamic financial literacy on doom spending behavior among female Generation Z e-commerce users, specifically students of the Islamic Banking Study Program, class of 2022, at the State Islamic University of North Sumatra. his study used a quantitative approach with a survey method on 50 female students selected using a purposive sampling technique. Data were collected through a five-point Likert scale questionnaire consisting of 9 items of Islamic financial literacy and 9 items of doom spending behavior. The analysis was carried out in two stages: (1) Item Response Theory with a Graded Response Model to evaluate the quality of the instrument and estimate the latent scores of each construct, and (2) Generalized Structural Equation Modeling (GSEM) to test the structural relationship between the latent variables of Islamic financial literacy and doom spending behavior. The analysis results show that all items in both constructs have very high discrimination parameters, thus the instrument is able to adequately represent the latent constructs. The structural model estimation results indicate that Islamic financial literacy has a positive influence on doom spending behavior with a marginal significance level (β = 0.355; p = 0.061). These findings indicate that increasing Islamic financial literacy has not been able to fully suppress the tendency towards doom spending without being accompanied by stronger emotional control and internalization of spiritual values ​​in facing a highly persuasive digital environment.